2015
DOI: 10.1080/03091929.2015.1076812
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of water waves by a pair of vertical porous plates

Abstract: The two-dimensional problem of scattering of small-amplitude surface water-waves by two symmetric vertical thin porous plates is investigated here assuming the linear theory. The problem is formulated in terms of two hypersingular integral equations of the second kind involving the discontinuities in the unknown symmetric and antisymmetric potential functions describing the motion in the fluid across one of the plates. Exploiting the conditions at the two tips of the plate, the discontinuity is approximated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…3. The corresponding curves of Gayen and Mondal [16] for two equal plates almost coincide with the corresponding curves in Fig. 3.…”
Section: Comparison With Existing Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…3. The corresponding curves of Gayen and Mondal [16] for two equal plates almost coincide with the corresponding curves in Fig. 3.…”
Section: Comparison With Existing Resultssupporting
confidence: 73%
“…To further verify the results obtained for permeable plates in this study, we compare our results with those reported by Gayen and Mondal [16], who used a different method for analyzing two equal plates. Gayen and Mondal [16] plotted |R| against dimensionless wave number K(d+b) (≡ Kl 2 here) for three different values of µ = d−b d+b (≡ l 1 l 2 = l 3 l 2 here) and fixed value of the length of separation of plates and porosity and normal incident wave in their Fig. 4.…”
Section: Comparison With Existing Resultssupporting
confidence: 63%
See 1 more Smart Citation